Strategic Planning for Wolio Language Maintenance in An Effort to Optimize the Use of Regional Languages in Baubau City - Yunus, Yunus; Niampe, La; Karno, Edy; Konisi, La Yani (Journal of Neonatal Surgery, 2025)
The objectives of this research are to: (1) identify and analyze the role of internal factors in the preservation of the Wolio language in Baubau City; (2) identify and analyze the external factors influencing the preservation of the Wolio language in Baubau City; and (3) formulate strategic planning for the preservation of the Wolio language to optimize the use of regional languages in Baubau City. This study uses both qualitative and quantitative methods. Data were collected through observation, interviews, documentation, and questionnaires. The data were analyzed using the SWOT analysis method. The results show that the role of internal factors in the preservation of the Wolio language in Baubau City falls into several categories: a) language preservation within families is still dominant among speakers over the age of 50, whereas families either older or younger than this age group who live in multiethnic environments tend to use Indonesian or mixed languages; b) local communities play a role in preserving the Wolio language; and c) traditional institutions, religious leaders, and community figures continue to uphold the use of the Wolio language in various activities. External factors also play a significant role in preserving the Wolio language in Baubau City, particularly through: a) national policies such as Law Number 24 of 2009 Article 42 Paragraph 1, Regional Regulation No. 2 of 2022 concerning the Preservation and Development of the Wolio Language, Literature, and Script, and Mayor Regulation No. 17 of 2023 on the local curriculum of Wolio language and script at the elementary and junior high school levels, as well as initiatives by the Southeast Sulawesi Language Center through language revitalization; and b) collaboration between academics, the government, the Southeast Sulawesi Language Center, traditional leaders, cultural figures, and literacy activists. The SWOT-4K analysis of the Wolio language preservation strategy resulted in an IFAS score of 3.232 and an EFAS score of 3.251, indicating that an aggressive strategy is the most appropriate, as it shows strong internal capabilities and promising opportunities for preserving the Wolio language, especially in Baubau City.